Globalized policies for teacher training: proposals for a philosophical reading - Galazzi, Laura; Gómez, Diana; Vázquez, Muriel (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The present article explores teacher training policies promoted by international organizations including the World Bank or the OECD in Latin America and the Caribbean. Documents edited by these organizations are addressed; three cross-cutting themes are used for reading them. First, socioeconomic hierarchies and their impact on the formulation of desirable teacher profiles are reviewed. Second, the genre assumptions inferred from the given information are reviewed. Finally, a reflection is made on the cultural traits that are assumed and expressed as desirables in the continued training of future teachers. Since it is a philosophical text, a problematic area is opened up for each of these themes, which remains available for reflection, discussion, and the study of the education system actors in each context. The conclusions suggest some open lines of research that constitute efforts to reformulate and intervene in teacher training processes, and concomitantly, in the definition of significant and emancipatory education policies in Latin America.